Ship squat in water of varying depth - Gourlay, Tim (Royal Institution of Naval Architects, 2003)
Two theories are described which predict ship squat in water of varying depth. Firstly, a one-dimensional theory is proposed for a ship in a narrow channel of varying depth. This is solved analytically in the case of a step depth change, and numerically for general depth profiles. Secondly, a slender-body theory is discussed for wider channels or open water. A numerical method is developed and used to find the squat of a ship passing a step depth change.